1993
DOI: 10.1007/bf00236092
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing transient gene expression in bean (Phaseolus vulgaris L.) using an electrical particle acceleration device

Abstract: The parameters influencing transient expression of the betaglucuronidase gene in bean embryonic axes, cotyledons, apical meristems and leaves were evaluated after gene delivery with an electrical particle acceleration device. A calciumspermidine procedure for coating gold particles with DNA resulted in higher levels of GUS expression with lower concentrations of gold particles compared with a calcium phosphate procedure. The DNA concentration, distance between the discharge chamber and the retaining screen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Transient gene expression is influenced by several factors including species and physiological status of the explant [52], transformation parameters [53], [54], timing of gene integration [55], cell death and loss of DNA [56], [57], and gene structure [58]. PTGS also plays an important role in the post-introduction gene expression decline, so-called transient expression [39], [59].…”
Section: Discussionmentioning
confidence: 99%
“…Transient gene expression is influenced by several factors including species and physiological status of the explant [52], transformation parameters [53], [54], timing of gene integration [55], cell death and loss of DNA [56], [57], and gene structure [58]. PTGS also plays an important role in the post-introduction gene expression decline, so-called transient expression [39], [59].…”
Section: Discussionmentioning
confidence: 99%
“…Nonwrinkled seeds were then rinsed three times and soaked overnight in sterile deionized water. Apical meristems were exposed by removing cotyledons and primary leaves as described by Aragão et al (1993). Subsequently, the root tips were also excised.…”
Section: Methodsmentioning
confidence: 99%
“…The applicability of the particle bombardment to introduce and transiently express genes into dry bean was demonstrated in the beginning of 1990s (Genga et al 1992;Aragão et al 1992Aragão et al , 1993. The bombardment of meristematic cells of embryonic axes revealed that foreign genes could efficiently reach the superficial cell layers, demonstrating the feasibility of producing transgenic bean using this method (Aragão et al 1993). Russell et al (1993) reported the production of transgenic navy bean plants using an electrical particle acceleration device.…”
Section: Transformationmentioning
confidence: 99%